2013
DOI: 10.1159/000354439
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Exercise Restores Pancreatic Beta-Cell Function and Autonomic Nervous System Activity in Obese Rats Induced by High-Fat Diet

Abstract: Background/Aims: Metabolic syndrome has been identified as one of the most significant threats to human health in the 21st century. Exercise training has been shown to counteract obesity and metabolic syndrome. The present study aimed to investigate the effects of moderate exercise training on pancreatic beta-cell function and autonomic nervous system (ANS) activity in rats fed a high-fat diet (HFD). Methods: Weaning rats were divided into four groups: rats fed a standard chow or HFD (sedentary, Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 42 publications
5
33
2
Order By: Relevance
“…The data of the current research reveal, for the first time, that higher vagal nerve activity is observed in obese rats induced by early overfeeding. Our group also observed this feature in other different model of obesity [19,20,27,34], in all of these obesity model high fasting insulinemia and insulin resistance were observed. The method used in the present work cannot discriminate afferent from efferent signals; however, the firing rates from control rats are very similar to those reported by other authors [35,36].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The data of the current research reveal, for the first time, that higher vagal nerve activity is observed in obese rats induced by early overfeeding. Our group also observed this feature in other different model of obesity [19,20,27,34], in all of these obesity model high fasting insulinemia and insulin resistance were observed. The method used in the present work cannot discriminate afferent from efferent signals; however, the firing rates from control rats are very similar to those reported by other authors [35,36].…”
Section: Discussionsupporting
confidence: 79%
“…In previous studies, using the same exercise training protocol applied throughout life, we showed that obese rats induced by high-fat diet restores the imbalanced autonomic function beyond other metabolic dysfunctions [27]. Similar results were obtained in rats fed hypercaloric diets that ran voluntarily [39].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…After a stabilization of the signal over the course of 2 min, 20 record frames of 15 s were randomly chosen from each animal for spike counting. The average number of spikes was used to calculate the rate of nerve firing for each rat (Gomes et al 2013).…”
Section: Electrical Activity Of Vagus Nervousmentioning
confidence: 99%